Enterprise Breeding System Launch | Ibnou Dieng's interview - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
In this video, IITA's Head of Biometrics, Ibnou Dieng shares his thoughts on the EBS Program.